PERBEDAAN HASIL PEMERIKSAAN JUMLAH LEUKOSIT ANTARA METODE MANUAL IMPROVED NEUBAUER DENGAN METODE AUTOMATIC HEMATOLOGY ANALYZER - Satya Darmayani; Fonnie Ester Hasan; Devi Ekafitria A. (Jurnal Kesehatan Manarang, 2016)
Leucocytes are nucleated cells in the blood that can be divided into 5 types. Every cell can be calculated its percentage in the blood by doing types calculation and can be distinguished by the size of the core form, color of granules and cytoplasm inside. This study aimed to determine the results of the difference calculation of leukocytes count examination between Manual Method (Improved Neubauer) and Automatic Hematology Analyzer Method in outpatients at the General Hospital of Kendari. Samples of this study were 30 people taken by accidental sampling. The results of the study with 30 samples using manual method (Improved Neubauer), 25 patients (83.4%) had normal leukocyte and 5 patients (16.6%) had abnormal, and examination using Automatic Hematology Analyzer Method showed 22 patients (73.4%) had normal leukocyte and 8 patients (26.6%) had abnormal. Based on paired test of samples obtained p value = 0, 000, so it can be concluded that there is significant difference between count examination of leukocytes using Manual Method with Improved Neubauer and Automatic Hematology Analyzer Method.